Simulation Research on the Corrosion Behavior of X70 Pipeline Steel under Dynamic AC Interference - CAO Guofei, QIU Chunbin, ZHAO Dongye (Cailiao Baohu)
In order to provide reference for the anti-corrosion design of pipelines near electrified railways，the characteristics of AC dynamic interference parameters near pipelines of different railway types were studied on the basis of pipeline monitoring data.The corrosion behavior of buried X70 pipeline steel under dynamic AC interference in high-speed and ordinary railways was studied and analyzed through using a dynamic AC corrosion simulation test device under cathodic protection.Results showed that in a typical dynamic interference cycle，a higher dynamic AC interference current density resulted in a higher corrosion rate of X70 steel under the same cathodic protection potential.When the dynamic AC current density was higher than 100 A/m2，the corrosion rate was higher than 0.03 mm/a under any cathodic protection conditions.Under dynamic communication interference，as the level of cathodic protection increased，the corrosion rate presented a “saddle shaped”pattern，first decreasing and then increasing.Only when the AC current density was 30 A/m2 and the cathodic protection level was between－0.90 and－1.15 V (vs CSE)，the corrosion rate was less than 0.03 mm/a.Furthermore，even if the pipeline was in an effective cathodic protection state，corrosion would occur under dynamic communication interference.